Implementation of the Problem Based Learning Learning Model in Increasing the Motivation of Man 1 Kuningan Students - Komar, Komarudin Humaedi; Gumiandari, Septi; Xavier, Murphy; Elliot, McCarty (Journal International Inspire Education Technology, 2023)
In learning, teachers need a learning approach that can foster their motivation to learn. An educator is required to be able to design and choose a learning model that suits the needs of students. The problem-based learning model is one of the educational models that can help students develop problem-solving skills so that they can improve student learning outcomes and motivation. This study aims: (1) to determine the increase in extrinsic motivation through the problem based learning model; (2) To find out the learning outcomes and cooperative attitudes of students after using the problem based learning model. This study uses a qualitative approach by conducting interviews based on a list of questions to the informants. The results of this study prove that the application of the problem-based learning model can increase student learning motivation and also increase student knowledge and increase student learning outcomes. This is evident from the results of observations and the results of interviews that have been conducted, and the results obtained are: (1) Implementation of learning using the PBL model increases learning motivation, (2) student learning outcomes through problem-based learning are better than before. This shows that in implementing the lesson plan using the PBL model, it fosters students' curiosity about the material provided by the teacher and increases their understanding. The material provided by the teacher increases in the PBL model. The PBL model has a positive impact on learning activities.